Synthesis, characterization and application of novel cationic and amphoteric flocculants based on amylopectin - Kumar K.; Adhikary P.; Karmakar N.C.; Gupta S.; Singh R.P.; Krishnamoorthi S. (My University, 2025)
The synthesis of novel cationic flocculants based on amylopectin (AP), acrylamide (AM) and (3-acrylamidopropyl) trimethylammonium chloride (ATMAC) were done by free radical polymerization using ammonium persulphate (APS) as an initiator. Three different grades of novel cationic flocculants (AP-g-C 1 to AP-g-C 3) were synthesized by varying the proportion of acrylamide and (3-acrylamidopropyl) trimethylammonium chloride monomers. Through the hydrolysis of these flocculants, in presence of NaOH, three different grades of amphoteric polymers (AP-AT-C 1 to AP-AT-C 3) were synthesized. The synthesized polymers were characterized by various methods, namely, infrared spectroscopy, NMR spectroscopy, thermal analysis, viscosity measurement, scanning electron microscopy and X-ray diffractometry. The flocculation performance of AP-g-C and AP-AT-C were studied in kaolin suspension using jar test and settling test methods at neutral pH. Dye (Methylene blue) removal tests were performed using polymer beads and analysed by UV-vis spectroscopy. © 2015 Elsevier Ltd. All rights reserved.